Friend and foe: β-cell Ca2+ signaling and the development of diabetes - Paul V. Sabatini; Thilo Speckmann; Francis C. Lynn (Elsevier, 2019)
Background: The divalent cation Calcium (Ca2+) regulates a wide range of processes in disparate cell types. Within insulin-producing β-cells, increases in cytosolic Ca2+ directly stimulate insulin vesicle exocytosis, but also initiate multiple signaling pathways. Mediated through activation of downstream kinases and transcription factors, Ca2+-regulated signaling pathways leverage substantial influence on a number of critical cellular processes within the β-cell. Additionally, there is evidence that prolonged activation of these same pathways is detrimental to β-cell health and may contribute to Type 2 Diabetes pathogenesis. Scope of review: This review aims to briefly highlight canonical Ca2+ signaling pathways in β-cells and how β-cells regulate the movement of Ca2+ across numerous organelles and microdomains. As a main focus, this review synthesizes experimental data from in vitro and in vivo models on both the beneficial and detrimental effects of Ca2+ signaling pathways for β-cell function and health. Major conclusions: Acute increases in intracellular Ca2+ stimulate a number of signaling cascades, resulting in (de-)phosphorylation events and activation of downstream transcription factors. The short-term stimulation of these Ca2+ signaling pathways promotes numerous cellular processes critical to β-cell function, including increased viability, replication, and insulin production and secretion. Conversely, chronic stimulation of Ca2+ signaling pathways increases β-cell ER stress and results in the loss of β-cell differentiation status. Together, decades of study demonstrate that Ca2+ movement is tightly regulated within the β-cell, which is at least partially due to its dual roles as a potent signaling molecule. Keywords: β-cells, Diabetes, Ca2+, CREB, NFAT, Calmodulin, Calcineurin, CaMK